Present and future needs for nurses. Issue 1 (27th February 2018) - Daniel, Kathryn M.; Smith, Christina Y.
Abstract : This review outlines the major contributors of the present and future needs for nursing in the United States as well as how the situation impacts the vision and goals of the National Institute for Nursing Research (NINR). This is a review and is based on current published literature. There is a relative nursing shortage even though the production of new nurses has been greatly increased since 2010. This is due to the delayed retirement of many baby boomer nurses, and millennials who are more likely to choose nursing as a profession than previous cohorts. However, the numbers and geographic distribution of baby boomer nurses will not be matched by millennials in the pipeline. At the same time, the need for nurses in the healthcare workforce is increasing due to expanded roles and sites for care. Compounding this, only a very small percentage of the whole of nurses choose to be involved in research. In order for nurses to be involved in making contributions to address the vision and goals of NINR, the continued aggressive growth and development of the nursing workforce is needed.